The Effects of Intellectual and Cultural Orientalist Invasion on Islamic Studies: An Analytical Study (Journal of the College of Basic Education, 2026)
The Islamic world has, over past centuries, witnessed a wave of non-military invasion manifested in Western attempts to influence Islamic thought and culture. This invasion took shape through Orientalism, which was not merely an academic activity concerned with the study of Islam, but rather a knowledge-based tool serving political, colonial, and religious objectives. This intellectual assault focused on dismantling the doctrinal structure and the traditional authoritative references of the Islamic world through distorted studies and biased analytical approaches, resulting in profound intellectual consequences.The foundations of this research address the most significant manifestations and motives that drove some Orientalists to launch attacks aimed at distorting the image of Islam, misrepresenting the Holy Qur’an, as well as the character of the Prophet Muhammad (peace be upon him), Islamic law, and Islamic history.However, Islam presented a different perspective. It emerged holding a lifeline of salvation, achieving complete success for the world at a moment when it was on the brink of total destruction. People entered Islam in large numbers, and Islam united them, melting their differences of race and color into a single crucible, from which a solid, radiant alloy was formed. All of this was nothing but the brilliance of faith.